Investigation of the bacterial diversity in fermented mangrove apple (Sonneratia caseolaris) fruit juice kombucha using DNA metabarcoding - JELENA ANGEL VISAKHADEVI; SAPTO ANDRIYONO; WORO HASTUTI SATYANTINI; NUR IZZATI MOHD NOH (Society for Indonesian Biodiversity, 2024)
Abstract. Visakhadevi JA, Andriyono S, Satyantini WH, Noh NIM. 2024. Investigation of the bacterial diversity in fermented mangrove apple (Sonneratia caseolaris) fruit juice kombucha using DNA metabarcoding. Biodiversitas 25: 3201-3207. Kombucha, a functional beverage produced from the symbiosis between bacteria and yeast, varies in microbial composition and biological activity depending on the raw materials used for fermentation. This study investigated the potential of mangrove apple (Sonneratia caseolaris (L.) Engl.) fruit juice as a novel substrate for kombucha fermentation because of its high nutritional value and underutilization. We analyzed the bacterial composition of kombucha using a molecular metabarcoding approach with the universal 16S rRNA primers 27F (AGA GTT TGA TCM TGG CTC AG) and 1492R (GGT TAC CTT GTT ACG ACT T). The optimal bacterial density was observed on the 8th day of fermentation, with a value of 1.402. The pH progressively decreased during the fermentation period. This study successfully explored the diversity of bacteria in kombucha grown in apple fruit juice. The dominant bacterial taxon was acetic acid bacteria, with 75,009 reads for Acetobacteraceae. At the genus level, Komagataeibacter was predominant, with 74,660 reads, and at the species level, Komagataeibacter saccharivorans was the most abundant, with 67,502 reads. These results suggest mangrove apple fruit juice as the viable substrate for kombucha fermentation that supports a rich microbial community. This study highlights the potential of alternative substrates, such as mangrove apple fruit juice, to enhance kombucha's microbial diversity and health benefits.